Answer: Choice B. 3 - 3x
Work Shown:
![g(x) = -x\\\\g(f(x)) = -f(x)\\\\g(f(x)) = -(3x-3)\\\\g(f(x)) = -3x+3\\\\g(f(x)) = \boldsymbol{3-3x}\\\\](https://img.qammunity.org/2022/formulas/mathematics/high-school/nn1jpb3cnux1v95cfqdtk899r3669xp6kc.png)
Explanation: We start with the outer function g(x). In the second step, we replace every copy of x with f(x). From there we plug in f(x) = 3x-3 and simplify using the distribution rule.
The notation
is the same as writing
![(g \circ f)(x)](https://img.qammunity.org/2022/formulas/mathematics/high-school/avadkrtq7vlrlafvhni0vwiqn2j3x3ia7n.png)